An Operational Perspective Of My Organization: KP Quality Products Manufacturing Sendirian Berhad - Ramasamy, Katheresan (2002)
KP Quality Manufacturing Sdn. Bhd. (KPQP) is a company which is divided in four section with each section having independent facilities to cater for Aerosol filling, household products, beverages and toiletries.